The Nutrient Content of Paspalum atratum Grass Associated with Macroptilium lathyroides Legume Inoculated with Rhizobium through the Application of Molybdenum and Phosphorus Fertilizers - Trisnadewi, Anak Agung Ayu Sri; Suarna, I Wayan; Mahardika, I Gede; Suryani, Ni Nyoman (International Journal of Environment, Agriculture and Biotechnology, 2021)
The experiment aimed to increase the nutrient content of Paspalum atratum grass associated with Macroptilium lathyroides legume inoculated with Rhizobium through the application of molybdenum (Mo) and phosphorus (P) fertilizer. The experiment used randomized block design (RBD) with factorial pattern. The first factor was Rhizobium inoculation consisted of Mo and P fertilizers without Rhizobium inoculation (R0) and with Rhizobium inoculation (R1). The second factor was planting pattern: grass monoculture (A1), legume monoculture (A2), one row of grass between one row of legumes (A3), and one row of grass between two rows of legumes (A4). There were eight treatments and each combination was repeated three times so that there were 24 experimental plots. The results showed that application of R1 increased the nutrient content of forage. A3 and A4 treatments were increased the nutrient content of forage compared with A1 dan A2. The conclusion of the research that the association of Paspalum atratum grass and Macroptilium lathyroides legume inoculated with Rhizhobium and fertilized with Mo and P was able to increase nutrient content.